Synonymic notes on European Lymexylidae (Coleoptera) - Nardi, Gianluca (Zootaxa, 2019)
Lymexylidae Fleming, 1821 are a small, extremely isolated saproxylic family (Lawrence 2010) comprising only four species in Europe (Cuccodoro 2007). Some tropical species have been occasionally intercepted at various ports, but they have never become established (cf. Nardi 2004).